Genome‐wide analysis of Glycine soja ubiquitin (UBQ) genes and functional analysis of GsUBQ10 in response to alkaline stress. Issue 3 (28th August 2018) - Chen, Chao; Chen, Ranran; Wu, Shengyang; Zhu, Dan; Sun, Xiaoli; Liu, Beidong; Li, Qiang; Zhu, Yanming
Abstract : Ubiquitin is a highly conserved protein with multiple essential regulatory functions through the ubiquitin‐proteasome system. Even though its functions in the ubiquitin‐mediated protein degradation pathway are very well characterized, the function of ubiquitin genes in the regulation of the alkaline stress response is not fully established. In this study, we identified 12 potential UBQ genes in the Glycine soja genome, and analyzed their evolutionary relationship, conserved domains and promoter cis ‐elements. We also explored the expression profiles of G. soja UBQ genes under alkaline stress, based on the transcriptome sequencing. We found that the expression of GsUBQ10 was significantly induced by alkaline stress, and the function of GsUBQ10 was characterized by overexpression in transgenic alfalfa ( Medicago sativa ). Our results suggested that GsUBQ10 transgenic lines significantly improved the alkaline tolerance in alfalfa. The GsUBQ10 transgenic lines showed lower relative membrane permeability, lower malon dialdehyde content and higher catalase activity than in the wild‐type plants. This indicates that GsUBQ10 is involved in regulating the reactive oxygen species accumulation under alkaline stress. Taken together, we identified an ubiquitin gene GsUBQ10 from G. soja, which plays a positive role in responses to alkaline stress in alfalfa.